Hygienic Analysis Of Microclimate Indicators At Polymer Production Enterprises (Texas Journal of Medical Science, 2024)
During the study, unfavorable microclimate indicators were assessed at the Jizzakh enterprise for the production of polymer products. The microclimate indicators at the enterprise for the hot period of the year (July, August) differed somewhat from comfortable indicators. The air temperature in the workshop for the production of consumer goods was above the maximum permissible dose from 0,80C to 6,90C. In the workshop for the production of polyethylene products films from 3,60C to 5,50C, in the workshop for the production of polyethylene pipes - from 3,80C to 4,60C, and at workplaces in the workshop for the production of polyethylene components from 3,80C to 4,60C